2016
DOI: 10.1016/j.celrep.2016.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Fatty Acid Oxidation Restrains Systemic Catabolism during Starvation

Abstract: The liver is critical for maintaining systemic energy balance during starvation. To understand the role of hepatic fatty acid β-oxidation on this process, we generated mice with a liver-specific knockout of carnitine palmitoyltransferase 2 (Cpt2L−/−), an obligate step in mitochondrial long-chain fatty acid β-oxidation. Fasting induced hepatic steatosis and serum dyslipidemia with an absence of circulating ketones while blood glucose remained normal. Systemic energy homeostasis was largely maintained in fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 51 publications
10
108
1
1
Order By: Relevance
“…(Figure 1H). Previously, we had shown significant alterations in serum acylcarnitines in Cpt2 L−/− mice in response to a 24hr fast or feeding a ketogenic diet (Lee et al, 2016b). HFD-fed Cpt2 L−/− mice exhibited a dramatic suppression of free carnitine and acetyl-carnitine in both blood (Figure 1I) and urine (Figure 1J).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…(Figure 1H). Previously, we had shown significant alterations in serum acylcarnitines in Cpt2 L−/− mice in response to a 24hr fast or feeding a ketogenic diet (Lee et al, 2016b). HFD-fed Cpt2 L−/− mice exhibited a dramatic suppression of free carnitine and acetyl-carnitine in both blood (Figure 1I) and urine (Figure 1J).…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we showed that Cpt2 L−/− mice were relatively normal under carbohydrate-fed conditions, but the exposure of the liver to a high burden of free fatty acids via prolonged fasting or a ketogenic diet elicited profound cellular and physiological adaptations (Lee et al, 2016b). Since hepatic fatty acid oxidation is central to systemic energy balance, we were interested in how feeding a chronic lipid-rich diet to Cpt2 L−/− mice would affect systemic metabolic dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of mice in which exon 4 of the mouse Cpt2 gene is flanked by loxP sequences was previously described (35,36). To generate osteoblast-and osteocyte-specific KO, Cpt2 lox/lox mice were crossed with Osteocalcin-Cre (Oc-Cre TG/+ ) mice (37).…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the requirement for fatty acid β-oxidation during bone formation, we generated mice in which the Cpt2 gene that encodes Cpt2 was selectively disrupted in osteoblasts and osteocytes. Cpt2 lox/lox mice in which exon 4 is flanked by loxP sites (35,36) were crossed with Oc-Cre mice (37) ). Both male and female ΔCpt2 mice were born at the expected Mendelian frequency, exhibited 70% reductions in Cpt2 mRNA levels in skeletal tissue (Figure 2A) with normal expression levels in other metabolic tissues (Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.92704DS1), and maintained normal body weights ( Figure 2B).…”
Section: Skeletal Accumulation Of Fatty Acidsmentioning
confidence: 99%